Elasticity of demand in the mass transit subsystem of the West Center Metropolitan Area as a function on the increase in the fare (2020)
In this work is presented the demand elasticity of a passenger’s public transport system with respect to bus fares. First, we established confidence intervals with the information of passengers who has used the transport system by periods. Once it has been defined the confidence intervals then the demand elasticity with respect to bus fare its calculated. This estimation allows to conclude how much the bus fare impacts the demand of the service, or if it exists another reason why the demand of the services has fluctuated during the history of the system. In this research it can be observed that the three first periods were inelastic and the next three periods were elastic, in the last periods its necessary to do a holistic view to find which another factor it’s the one who is affecting the passenger’s demand.